2018
DOI: 10.1093/jn/nxy014
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Fats from Butter but Not from Cheese Increase HDL-Mediated Cholesterol Efflux Capacity from J774 Macrophages in Men and Women with Abdominal Obesity

Abstract: Abstract Background Recent evidence suggests that the association between dietary saturated fatty acids (SFAs) and coronary artery disease risk varies according to food sources. How SFAs from butter and cheese influence HDL-mediated cholesterol efflux capacity (CEC), a key process in reverse cholesterol transport, is currently unknown. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(43 reference statements)
2
9
0
1
Order By: Relevance
“…The study by Brassard et al 6 , is a secondary analysis of a randomly controlled intervention trial 9 that confirmed earlier reports that equivalent amounts of SFA from cheese had a lesser effect in elevating serum LDL-cholesterol than butter 10,11 . This was attributed to a food matrix effect of cheese that was proposed to reduce the absorption of SFA in the gut, and thus its capacity to raise LDL cholesterol.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…The study by Brassard et al 6 , is a secondary analysis of a randomly controlled intervention trial 9 that confirmed earlier reports that equivalent amounts of SFA from cheese had a lesser effect in elevating serum LDL-cholesterol than butter 10,11 . This was attributed to a food matrix effect of cheese that was proposed to reduce the absorption of SFA in the gut, and thus its capacity to raise LDL cholesterol.…”
supporting
confidence: 53%
“…The effects of dietary SFA on serum LDL-cholesterol depend on what macronutrient (unsaturated fatty acids and/or carbohydrate) replaces the SFA 4 , and other constituents in the food, including its specific SFA content, and other components of the food matrix, such as protein, minerals, fiber 5 . The study by Brassard et al 6 , examines these phenomena in relation to HDL-cholesterol, but extends its analysis to the substructure and function of HDL with relevance to the potential cardio-protective role of this lipoprotein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(74) SF from butter may have higher HDLmediated cholesterol efflux capacity that compensates for any LDL-cholesterol-raising effects from butter, resulting in a neutral association between butter and CVD risks. (75) The main sources of SF from plants are coconut oil and palm oil. Besides SF, palm oil also consists of oleic acids (monounsaturated) and linoleic acids (LAs; polyunsaturated), and vitamins A and E (antioxidants), which have cardioprotective properties.…”
Section: Possible Mechanisms and Specific Subtypesmentioning
confidence: 99%
“…Ensaios clínicos têm mostrado uma maior associação entre ácidos graxos saturados (AGS) da manteiga e aumento de LDL-C, em comparação aos AGS do queijo 40 e a outros tipos de gordura 41 . Apesar disso, estudos também têm relacionado o consumo de manteiga a maiores valores de HDL-C 41 e maior capacidade de efluxo de colesterol mediada pelo HDL-C, em comparação a uma dieta com AGS do queijo ou uma dieta com elevada quantidade de carboidrato 42 . Uma meta-análise de estudos prospectivos não encontrou associação significativa entre o consumo de manteiga com DCV, doença coronariana ou infarto, e uma associação inversa foi demonstrada para o diabetes.…”
Section: Estudo Longitudinal Deunclassified